Assessment of medication errors and adherence to WHO prescription writing guidelines in a tertiary care hospital - Dilnasheen Sheikh; Uday Venkat Mateti; Shamaprakash Kabekkodu; T. Sanal (SpringerOpen, 2017)
The objective of the study is to assess the medication errors and adherence to WHO prescription writing guidelines in a tertiary care hospital. A prospective observational study was carried out for a period of 8 months from June 2015 to February 2016 at tertiary care hospital. At inpatient department regular chart review of patient case records was carried out to assess the medication errors. The observed medication errors were assessed for level of harm by using NCCMERP index. The outpatient prescriptions were screened for adherence to WHO prescription writing guidelines. Out of 200 patients, 40 patients developed medication errors. Most of the medication errors were observed in the age group above 61 years (40%). Majority of the medication errors were observed with drug class of antibiotics 9 (22.5%) and bronchodilators 9 (22.5%). Most of the errors were under the NCCMERP index category C. Out of 545 outpatient prescriptions, 51 (9.37%) prescriptions did not have prescriber's name and all of the prescriptions lack prescriber's personal contact number. Eighteen prescriptions did not have patient's name and 426 (78.2%) prescriptions did not have patient's age. The prevalence of medication errors in this study was relatively low (20%) without any fatal outcome. Omission error was the most frequently observed medication errors 31 (77.5%). In the present study, the patient's age was missing in 78.2% of the prescriptions and none of the prescriptions had patient's address and the drug names were not mentioned by their generic names.